Formulasi Gel Pacar Air (Impatiens balsamina Linn.) terhadap Propionibacterium acnes dan Staphylococcus epidermidis - Ismarani, Diah; Pratiwi, Liza; Kusharyanti, Indri (Pharmaceutical Sciences and Research, 2014)
Acnes vulgaris is a chronic inflammatory disease of sebaceous follicles caused by Propionibacterium acnes and Staphylococcus epidermidis. The antibacterial activity of Impatiens balsamina L. has been studied for many years. The aims of this study are to find out the antiacne effect from methanolic extract of stems and leaves of Impatiens balsamina L. that formulated in gel. Simplicia were extracted using soxhlet technique bu using methanol as solvent. Extracts were then formulated in gel in three variations of HPMC 4000 and Carbopol 934 as gel base with ratio of 70:30 (F1), 50:50 (F2) and 30:70 (F3). The determination of antiacne effect was done using disc diffusion method. Evaluation of physical and chemical properties of those gels includes organoleptic examination, spreadability testing, adhesion testing and pH testing. Data were analyzed using R version 2.14.1 package R-commander. Determination results showed the diameter of inhibition zone from FI, FII and FIII for P.acnes are 6.46 ±0.15 mm; 12.16 ± 0.35 mm; 16.13 ± 0.35 mm and for S. epidermidis sebesar 14.5 ± 0.47 mm; 16.56 ± 0.651 mm; 17.13 ± 0.44 mm. Analysis results showed that gel of FIII gave optimal antiacne effect, and significantly different from positive control (p < 0,05). The evaluation of gel showed that they have homogeny texture, good spreadability and adhesion, as well as the pH.